Associations between teacher expectations and racial disproportionality in discipline referrals. (April 2021) - Santiago-Rosario, María Reina; Whitcomb, Sara A.; Pearlman, Jessica; McIntosh, Kent
Abstract: We explored the racial discipline gap and sought to understand the extent to which elementary school teachers' ( N = 33; Grades K-6) expectations for their students' ( N = 496) future outcomes predicted racial discipline disproportionality. We used multilevel models, and Ordinary Least Squares (OLS) regression with standardized errors corrected, to examine associations between teacher expectations of academic and behavioral student outcomes and patterns of office discipline referrals (ODRs) for the year. Results showed disproportionate ODR outcomes for Black students in comparison to White students. Additionally, we found that students held to lower expectations by their teachers received more ODRs than peers rated highly by their teachers, regardless of race. We also found that for every unit teacher expectations increased, the ODR disparity between Black, Latinx, and White students decreased. Lastly, multilevel models exploring teacher expectations of student outcomes explained approximately 21% of the difference in ODRs between Black and White peers.